2017
DOI: 10.1080/10408398.2017.1386159
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of coffee or caffeine and serum concentration of inflammatory markers: A systematic review

Abstract: Coffee consumption is associated with reduced risk of conditions that share low-grade inflammation as their physiopathological basis. We therefore summarized the effects of coffee or coffee components on serum levels of inflammatory markers. Clinical trials assessing the effect of coffee, caffeine or other coffee components on inflammatory markers were searched without restriction to publication date. Fifteen studies (8 involving coffee and 7 caffeine) were included. Increased adiponectin levels were found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 64 publications
4
50
0
Order By: Relevance
“…Several studies showed that consuming a moderate amount of caffeine has a protective effect against cancer [12], diabetes mellitus type 2 [13], inflammatory diseases and pain [14], Parkinson's and related neurodegenerative diseases [15], cardiovascular disease [16], and stroke [17]. Light to moderate caffeine intake has also been found to be associated with reduced risk of death [18] from all causes, including suicide [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that consuming a moderate amount of caffeine has a protective effect against cancer [12], diabetes mellitus type 2 [13], inflammatory diseases and pain [14], Parkinson's and related neurodegenerative diseases [15], cardiovascular disease [16], and stroke [17]. Light to moderate caffeine intake has also been found to be associated with reduced risk of death [18] from all causes, including suicide [19].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have suggested an anti-inflammatory role for caffeine, mainly inhibiting TNF-α production [10]. Regarding in vivo studies, only a few have addressed the effects of caffeine supplementation on blood inflammatory markers in humans [11]. These studies used a single dose of caffeine or used coffee as supplement when longer interventions were tested, reporting slight anti-inflammatory effects from the supplementation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…80 However, review of fifteen studies on the effect of coffee and caffeine on inflammation inferred the former had anti-inflammatory action, while the latter had complex effects on the inflammatory response with both proinflammatory and antiinflammatory responses reported. 81 Caffeine might have a neuroprotective role by regulating pathways that produce inflammatory molecules via adenosine receptors in brain cells. 82,83 Posttranscriptional regulation of LOXL1 gene expression has been also shown to be modulated by caffeine.…”
Section: Discussionmentioning
confidence: 99%